CUX2 deficiency causes facilitation of excitatory synaptic transmission onto hippocampus and increased seizure susceptibility to kainate - Toshimitsu Suzuki; Tetsuya Tatsukawa; Genki Sudo; Caroline Delandre; Yun Jin Pai; Hiroyuki Miyamoto; Matthieu Raveau; Atsushi Shimohata; Iori Ohmori; Shin-ichiro Hamano; Kazuhiro Haginoya; Mitsugu Uematsu; et al. (Scientific Reports, 2022)
Abstract CUX2 gene encodes a transcription factor that controls neuronal proliferation, dendrite branching and synapse formation, locating at the epilepsy-associated chromosomal region 12q24 that we previously identified by a genome-wide association study (GWAS) in Japanese population. A CUX2 recurrent de novo variant p.E590K has been described in patients with rare epileptic encephalopathies and the gene is a candidate for the locus, however the mutation may not be enough to generate the genome-wide significance in the GWAS and whether CUX2 variants appear in other types of epilepsies and physiopathological mechanisms are remained to be investigated. Here in this study, we conducted targeted sequencings of CUX2, a paralog CUX1 and its short isoform CASP harboring a unique C-terminus on 271 Japanese patients with a variety of epilepsies, and found that multiple CUX2 missense variants, other than the p.E590K, and some CASP variants including a deletion, predominantly appeared in patients with temporal lobe epilepsy (TLE). The CUX2 variants showed abnormal localization in human cell culture analysis. While wild-type CUX2 enhances dendritic arborization in fly neurons, the effect was compromised by some of the variants. Cux2- and Casp-specific knockout mice both showed high susceptibility to kainate, increased excitatory cell number in the entorhinal cortex, and significant enhancement in glutamatergic synaptic transmission to the hippocampus. CASP and CUX2 proteins physiologically bound to each other and co-expressed in excitatory neurons in brain regions including the entorhinal cortex. These results suggest that CUX2 and CASP variants contribute to the TLE pathology through a facilitation of excitatory synaptic transmission from entorhinal cortex to hippocampus.